A study on relationship between service quality and customer satisfaction: a case study of Melaka International Trade Centre (MITC) / Norazah Mohamed Yazid - Mohamed Yazid, Norazah (Faculty of Business and Management, 2007)
This research is about a study on relationship between service quality and customer satisfaction at Melaka International Trade Centre (MITC). Factors such as service quality and customer satisfaction have been identified in order to investigate whether or not these factors have a relationship with customer satisfaction.